Pseudo‑nitzschia fukuyoi (Bacillariophyceae), a domoic acid‑producing species from Nha Phu Bay, Khanh Hoa Province, Vietnam - Sing, Tung Teng (Springer Japan, 2015)
Two strains of Pseudo-nitzschia fukuyoi isolated from Vietnamese waters produce domoic acid, a toxin responsible for amnesic shellfish poisoning. Species identification was based on detailed morphological observation using a transmission electron microscope and also molecular data on large subunit (LSU) and the second internal transcribed spacer (ITS2) with NCBI nucleotide Blast (blastn). Toxin productivity of the two strains was confirmed and their range were 3.85–4.54 pg/cell by analyses using LC–MS/MS. This is the first report of occurrence of P. fukuyoi in Vietnamese waters, and the first confirmation of productivity of domoic acid of the species.